Implementasi Bagi Penyandang Disabilitas dalam Perolehan Surat Izin Mengemudi (SIM) ”D” di Polresta Denpasar - Saraswati, Cinta; Agus Kurniawan, I Gede (Fakultas Syariah INSURI Ponorogo, 2023)
Granting of Driver's Licenses (SIM) to persons with disabilities The obstacles faced by the Police in providing a driver's license (SIM) for persons with disabilities in the jurisdiction of the Denpasar Police, that in accordance with the provisions of the application for a driver's license must be completed with a Health Certificate from a doctor. This writing uses an emperical research method, namely conducting field research through interviews at the research site supported by primary and secondary data collected and processed in a qualitative descriptive manner. The Effectiveness of Driver's License (SIM) Making Services in the Administrative Unit (Satpas) of the Denpasar Police Driver's License, that the process of servicing a driver's license (SIM)